Utilization of Bio-Municipal Solid Waste Improves Saline-Sodic Soils and Crop Productivity in Rice-Wheat. Issue 1 (2nd January 2020) - Zaman, Gohar; Murtaza, Behzad; Imran, Muhammad; Shahid, Muhammad; Shah, Ghulam Mustafa; Amjad, Muhammad; Naeem, Muhammad Asif; Mubeen, Muhammad; Murtaza, Ghulam
Abstract: Solid waste management and soil degradation are the two main issues faced by the developing countries. The present study is the first effort to use bio-municipal solid waste (MSW) for the amelioration of saline-sodic soils of Pakistan. A pot experiment was conducted to evaluate the effects of MSW, farm yard manure (FM) and gypsum application on nitrate leaching, soil physicochemical characteristics and crop productivity under rice-wheat cropping system. The MSW was aerobically composted alone (MSW compost) or with FM (MSW_manure compost) or buried underground in lined pit for anaerobic decomposition (buried MSW) . Maximum nitrate leaching was observed during rice (84.91 mg L −1 ) and wheat (46.18 mg L −1 ) with buried MSW as compared with control treatment. Results showed that buried MSW significantly (p < 0.05) lowered the soil pHs (-5.6%), electrical conductivity (-38.8%), calcium carbonate (-45.8%), and sodium adsorption ratio (-51.4%) and significantly increased the organic matter (86.3%) and cation exchange capacity (31.50%) as compared with control treatment. Path analysis showed the highest direct path coefficient during rice and the lowest one during wheat. Soil amelioration with organic amendments was further confirmed with multivariate analysis. This study has proved that buried MSW can be used as an effective solution for MSW disposal thereby improving soil physicochemical properties and crop productivity from saline-sodic soil.